Implementation Of DeLone And McLean Models To Measure The Success Of Online-Based Tutoring System - Dedi Saputra; Haryani Haryani; Artika Surniandari; Juniato Sidauruk (Bulletin of Computer Science and Electrical Engineering, 2023)
Online learning system or better known as tutoring "bimbel" online is one of the learning methods that are delivered electronically using a computer device or smartphone and connected to the internet. Online tutoring is designed to enable distance learning through the internet without having to come face-to-face with the teacher. Rumah Belajar is a learning portal prepared by the Ministry of Education and Culture containing more than 12,934 learning materials. This portal can be utilized by students as an alternative to getting learning materials, be it inside or outside school hours. This research uses DeLone and McLean success model which only uses variable information quality, system quality, service quality, and user satisfaction. From the results of questionnaire collection, as many as 100 respondents provided th e data information needed in this study. The data is processed with Structural Equation Modeling (SEM) application using AMOS22 application. It is expected that with this research can be obtained recommendations about the learning system or online learning guidance that is good and liked by many users.